Konsep Tauhid Mengenai Jenis -Jenis Tauhid Bahaya Syirik dan Pentingnya Menjaga Tauhid - Maura Nur Aysa; Ririn Eriska; Anggun Fadhilah; Anugrah Dimas Wijaya; Iqbal Barory; Arini Julia (STKIP Subang, 2025)
Tawhid is the fundamental foundation of Islamic teachings, affirming the so oneness of Allah SWT in His essence, attributes, and actions. This study aims to provide a comprehensive analysis of the concepts of Tawhid, including Tawhid Rububiyyah, Tawhid Uluhiyyah, and Tawhid to Asma’ wa Sifat, as well as discussing the forms of shirk that oppose the purity of monotheism. Using a qualitative approach and library research, this study examines classical and contemporary literature to highlight the significance of Tawhid in shaping a Muslim’s character, worship practices, and spiritual consistency. The findings reveal that a correct understanding of Tawhid greatly influences the development of moral character, sincerity in worship, and steadfastness in faith. Moreover, thestudy is emphasizes the severe danger posed by shirk both major and minor which can corrupt belief and invalidate one’s deeds. Therefore, preserving Tawhid is essential for every Muslim in order to achieve ultimate success in this life and the hereafter.